Judging Statutes: Thoughts on Statutory Interpretation and Notes for a Project on the Internal Revenue Code - Lee Epstein; Nancy Staudt; Peter J. Wiedenbeck (Washington University Journal of Law & Policy, 2003)
The more interesting features of the non-normative literature on statutory interpretation lie not in the distinctive conclusions it has generated, but rather in its commonalities. We see two as particularly interesting. First, many of the relevant studies focus on civil rights legislation. This holds true regardless of whether the work’s producers are legal academics or social scientists, whether the research is primarily qualitative or quantitative, or whether it finds its theoretical grounding in psychology, sociology, or economics. Second, almost all the studies—especially those of the large-n, quantitative variety—explore the outcomes reached by jurists, and not the rationale or justifications they invoke. To be sure, the outcomes under investigation differ from study to study—sometimes it is support for the government or not; in others, it is whether the judge reached a “liberal” or “conservative” decision. However, the unmistakable focus is on the result, to the neglect of the rationale. These are not criticisms of the extant literature. Quite the opposite: we firmly believe that by investigating outcomes reached in civil rights cases, this line of inquiry has revealed a great deal about the “judicial mind.” At the same time, we believe just as firmly that if we are to fully understand the determinants of statutory interpretation, then a continued emphasis on civil rights is, for reasons we specify in Part I, a potential problem. And, to the extent that we desire a more comprehensive picture of judicial behavior, an exclusive focus on outcomes is, for reasons we elaborate on in Part II, incomplete at best and misleading at worst. Accordingly, we have devised a project that aspires to address these concerns by (1) exploring Supreme Court tax opinions, a body of case law that, despite its importance, has received virtually no systematic attention, and (2) analyzing or taking into account both outcomes and rationales. At the end of the day, we hope that our attention to these matters will make a useful contribution to the literature on judging statutes.
Keywords: Law -- Interpretation & construction; Judicial process; Taxation; Social science research